Foliar Cellulose and Lignin Degradation of Two Dominant Tree Species in a Riparian Zone of the Three Gorges Dam Reservoir, China - Chen, Zhangting; Chen, Xuemei; Wang, Chaoying; Li, Changxiao (Frontiers in Plant Science, 2020)
The riparian zone can affect the degradation of foliar cellulose and lignin by changing the hydrological gradient of the foliage decomposition environment. However, their degradation dynamics during the process of foliage decomposition remain unclear in mixed plantation forests in a riparian zone. Herein, we explored degradation of cellulose and lignin for two dominant riparian species, bald cypress (Taxodium distichum (L.) Rich.) and Chinese willow (Salix matsudana Koidz.), and a combined treatment with equal proportions of foliar mass of these species, involving three water treatments [no submergence (CK), shallow submergence (SS), and deep submergence (DS)] in a riparian zone of the Three Gorge Dam Reservoir, China. Throughout an entire year’s incubation, the degradation of cellulose and lignin was 55.57%–97.76% and 79.87%–93.82%, respectively. In the early stage of decomposition (i.e., the first 30 days), cellulose and lignin were rapidly degraded, and the mass loss of cellulose and lignin in water environments (SS and DS) was greater than that in a non-flooded environment (CK) regardless of the foliage type. The degradation of cellulose and lignin was mainly related to the quality of the leaf-litter (as indicated by the concentrations of cellulose and lignin, and the contents of C, N and P), decomposition period and local environmental factors (temperature, water gradients, and dissolved oxygen). Our results will provide a clear insight into the material cycling process in a riparian zone of the Three Gorge Dam Reservoir and similar ecosystems in other regions.